Effects of exposure to ozone at different stages in the development of Plantago major L. on chlorophyll fluorescence and gas exchange - Reiling, K (The New phytologist, 1994)
Similar ozone treatments were applied at different stages of growth to a population of Plantago major L., which is as sensitive to ozone as Bel-W3 tobacco. Plants were grown from seed for 8 wk in controlled-environment chambers and exposed to 70 μl O3 l-1 7 h d-1 for the whole period or for 2-wk episodes during weeks 1 + 2, 3 + 4, 5 + 6 or 7 + 8. Controls had charcoal-filtered air. Effects on stomatal conductance, chlorophyll fluorescence and net photosynthesis are described. The fluorescence character, t1/2 , proved to be very sensitive to ozone, and it responded at all stages of plant development, but the ratio of variable to maximum fluorescence decreased only when plants received ozone during the first 2 wk of growth. The reduction was caused by a drop in maximum fluorescence. Ozone had no effect on F0 . Whenever exposure occurred, O3 significantly reduced net CO2 assimilation and increased stomatal conductance. Unlike t1/2 , the effects were persistent, affecting leaves that were in bud or enshrouded by leaves when the exposure occurred. It is suggested that these persistent effects may have been caused by changes in resource allocation, flowering and senescence, which resulted in altered hormonal balance